Evaluation Of Fulfillment Of Pharmacy Service Standards In Clinical Pharmacy Services For Analgesic Drugs At Wijaya Pharmacy Health Of Kediri District - Titis Surya A; Fidi Setyawan; Adi Wibisono; Chinthia Devientasari (Strada Journal of Pharmacy, 2024)
Pharmaceutical services are services related to pharmaceutical preparations such as drugs recommended for the treatment of improving the quality of life of patients. The government has made efforts to improve health services, including the construction of various health facilities such as pharmacies. In accordance with PMK Number 73 of 2016 concerning Standards of Clinical Pharmacy Services in Pharmacies, this study was conducted with the aim of determining the fulfillment of pharmaceutical service standards in clinical pharmacy services for analgesic drugs at the Wijaya Sehat Pharmacy, Kediri Regency, including clinical pharmacy services such as PIS, Counseling, DTM, and MDSE, along with the Attitudes and Behavior of pharmacists during service through patient or respondent perceptions. The research method uses a quantitative method with a cross-sectional research design, the tool used to conduct this study is a questionnaire using a Likert scale 1-4 (strongly agree, agree, disagree, strongly disagree). Sampling using accidental sampling technique of 120 respondents who purchased analgesic drugs. Instrument testing was conducted for validity and reliability in different places before conducting the study. The results obtained were that pharmaceutical services at Wijaya Sehat Pharmacy still carried out 2 services, namely PIS and Counseling, while DTM and MDSE had not been implemented due to limited human resources, there were no complaints related to Side Effects of Drugs (SED), there were no diseases that required DTM, and patients had a comfortable perception during service because pharmacists were polite and